Islamophobia and threat perceptions: explaining anti Muslim sentiment in the West - Ciftci, Sabri (My University, 2013)
This paper investigates the determinants of anti Muslim sentiment in the West. Starting from the premise that Islamophobic attitudes are more nuanced than a simple dislike of Muslims, I focus on specific forms of attitudes which link Muslims to violence and terrorism. Data from the Pew Global Attitudes Surveys is used to test three theories: perceived threat, social identity, and cognitive capabilities. A series of logit estimations are used for the empirical analysis of individual level data in the United States, Great Britain, France, Germany and Spain. The results show that perceived realistic and symbolic threat is the most significant source of Islamophobic attitudes in the West. While individuals cognitively differentiate between general feelings toward Muslims and their specific characteristics, higher levels of education significantly reduces negative sentiments. A good number of Westerners think of Muslims as violent individuals while some believe that they support al Qaeda. Citizens in the West are more likely to associate Muslims with terrorism if they feel threatened by their physical and cultural existence.
Keywords: Islamophobia; Western Europe; United States; Perceived threat; Social identity; Cognitive capabilities